Myelodysplastic syndrome in childhood: report of two cases with deletion of chromosome 4 and the Philadelphia chromosome - Dalla Torre, C. A.; Lee, MLD; Yoshimoto, M.; Lopes, L. F.; Niéro-Melo, Ligia [UNESP]; de Toledo, SRC; Andrade, JAD (Elsevier B.V., 2002)
We report two pediatric patients with unclassified myelodysplastic syndrome (MDS) by the French-American-British (FAB) group. Both cases had clinical and hematological peculiarities, which had not been described yet. The cytogenetic alterations were 4q deletion and the Philadelphia (Ph) chromosome which appeared at different moments of the disease. One patient showed the Ph chromosome at disease transformation and the other at diagnosis. The different breakpoints at 4q and the presence of Ph could be a marker of this form of MDS. The association of clinical and hematological findings suggests the possibility of a new group of pediatric MDS. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: myelodysplastic syndrome; Philadelphia chromosome; chromosome 4; deletion; cytogenetic; FAB group